2021
DOI: 10.1177/10732748211056691
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Family and Social Network on Tobacco Cessation Amongst Cancer Patients

Abstract: Continued smoking after a cancer diagnosis adversely affects outcomes, including recurrence of the primary cancer and/or the development of second primary cancers. Despite this, prevalence of smoking is high in cancer survivors and higher in survivors of tobacco-related cancers. The diagnosis of cancer provides a teachable moment, and social networks, such as family, friends, and social groups, seem to play a significant role in smoking habits of cancer patients. Interventions that involve members of patients’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The importance of social support for cancer patients, especially for smoking cessation, is essential. Other studies have shown that cancer survivors who experienced higher levels of social support were less likely to become smokers [ 19 ] and cancer survivors who rated their support system as rather low were more likely to continue smoking after diagnosis [ 36 ]. As our study shows conflicting results, the question arises as to whether support can also have a negative effect, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of social support for cancer patients, especially for smoking cessation, is essential. Other studies have shown that cancer survivors who experienced higher levels of social support were less likely to become smokers [ 19 ] and cancer survivors who rated their support system as rather low were more likely to continue smoking after diagnosis [ 36 ]. As our study shows conflicting results, the question arises as to whether support can also have a negative effect, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that have been shown to be associated with smoking patterns in cancer patients include several different factors such as age [ 16 ], level of education [ 17 ]; type of diagnosed tumor [ 16 ]; alcohol consumption [ 18 ], and received social support [ 19 ]. In the population of non-cancer smokers, even more associated factors were found, such as relationship [ 20 ] and having children [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stories from our participants demonstrated that repeated encouragement helped individuals who smoke to quit. Previous studies have confirmed that having support from healthcare providers [ 25 , 26 ], partners [ 27 ], family [ 28 ], and friends [ 28 , 29 ] increases successful smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Described as an event or circumstance that motivates an individual to take positive actions regarding their health, ‘teachable moments’ have been examined across an array of settings over the years to assess whether health events can motivate risk‐reducing behaviours. For example, HIV treatment initiation and smoking cessation (Vidrine et al, 2018 ), antenatal care visits and screening for sickle cell and thalassemia (Brown et al, 2011 ; Tsianakas et al, 2012 ), COVID‐19 crisis and lifestyle change in cardiovascular disease patients (Brust et al, 2021 ), ‘cancer worry’ and smoking cessation (McBride et al, 2008 ) and cancer screening, diagnosis, care and survivorship (Gray et al, 2021 ; Karvinen et al, 2015 ; Kathuria et al, 2020 ; McBride et al, 2017 ; Neumann et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%